Implementing a new birthing room design: a qualitative study with a care provider perspective - Lisa Goldkuhl; Malin Tistad; Hanna Gyllensten; Marie Berg (BMC, 2023)
Abstract Background Research shows that interventions to protect the sensitive physiological process of birth by improving the birthing room design may positively affect perinatal outcomes. It is, however, crucial to understand the mechanisms and contextual elements that influence the outcomes of such complex interventions. Hence, we aimed to explore care providers' experiences of the implementation of a new hospital birthing room designed to be more supportive of women's birth physiology. Methods This qualitative study reports on the implementation of the new birthing room, which was evaluated in the Room4Birth randomised controlled trial in Sweden. Individual interviews were undertaken with care providers, including assistant nurses, midwives, obstetricians, and managers (n = 21). A content analysis of interview data was conducted and mapped into the three domains of the Normalisation Process Theory coding manual: implementation context, mechanism, and outcome. Results The implementation of the new room challenged the prevailing biomedical paradigm within the labour ward context and raised the care providers' awareness about the complex interplay between birth physiology and the environment. This awareness had the potential to encourage care providers to be more emotionally present, rather than to focus on monitoring practices. The new room also evoked a sense of insecurity due to its unfamiliar design, which acted as a barrier to integrating the room as a well-functioning part of everyday care practice. Conclusion Our findings highlight the disparity that existed between what care providers considered valuable for women during childbirth and their own requirements from the built environment based on their professional responsibilities. This identified disparity emphasises the importance of hospital birthing rooms (i) supporting women's emotions and birth physiology and (ii) being standardised to meet care providers' requirements for a functional work environment. Trial registration ClinicalTrials.gov: NCT03948815, 14/05/2019.